Yo autobigráfico y figura (s) de autor en La tía Julia y el escribidor y El pez de agua de Mario Vargas Llosa - Negrete Sandoval, Julia Érika (El Colegio de México, 2019)
Convinced that behind the scenes of all writing it is possible todiscern the writer’s self-affirmation and (im)posture, and since studies on“authoriality” in Hispanic American literature continue to be on the rise, Ipropose to study the forms of autofiguration in Mario Vargas Llosa’s La tíaJulia y el escribidor and El pez en el agua. The autobiographical nature of bothbooks encompasses fundamental ideas about the author and authorship,that take the form of textual images that ask questions about who the writeris and what she/ he ought to be.